2017
DOI: 10.1002/jbmr.3241
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet Rectifies Hypercalcemia in a Patient With Familial Hypocalciuric Hypercalcemia Type 2 (FHH2) Caused by a Germline Loss-of-Function Gα11 Mutation

Abstract: G‐protein subunit α‐11 (Gα11) couples the calcium‐sensing receptor (CaSR) to phospholipase C (PLC)‐mediated intracellular calcium (Ca2+ i) and mitogen‐activated protein kinase (MAPK) signaling, which in the parathyroid glands and kidneys regulates parathyroid hormone release and urinary calcium excretion, respectively. Heterozygous germline loss‐of‐function Gα11 mutations cause familial hypocalciuric hypercalcemia type 2 (FHH2), for which effective therapies are currently not available. Here, we report a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 39 publications
1
58
0
2
Order By: Relevance
“…The effectiveness of cinacalcet in rectifying the FHH2‐associated loss‐of‐function abnormalities caused by the downstream Gα 11 protein has been assessed by in vitro and in vivo studies. Thus, recent in vitro studies have shown that cinacalcet improves the signalling responses of HEK293 cells stably expressing the CaS receptor (HEK–CaS receptor), which have been transiently transfected with FHH2‐associated Gα 11 mutants (Babinsky et al ., ; Gorvin et al ., ). Indeed, nanomolar doses of cinacalcet were demonstrated to rectify the impaired Ca 2+ i responses associated with loss‐of‐function Gα 11 mutations (Table ) (Babinsky et al ., ; Gorvin et al ., ).…”
Section: Calcimimetic Treatment For Hypercalcaemic Disorders Of the Cmentioning
confidence: 97%
See 4 more Smart Citations
“…The effectiveness of cinacalcet in rectifying the FHH2‐associated loss‐of‐function abnormalities caused by the downstream Gα 11 protein has been assessed by in vitro and in vivo studies. Thus, recent in vitro studies have shown that cinacalcet improves the signalling responses of HEK293 cells stably expressing the CaS receptor (HEK–CaS receptor), which have been transiently transfected with FHH2‐associated Gα 11 mutants (Babinsky et al ., ; Gorvin et al ., ). Indeed, nanomolar doses of cinacalcet were demonstrated to rectify the impaired Ca 2+ i responses associated with loss‐of‐function Gα 11 mutations (Table ) (Babinsky et al ., ; Gorvin et al ., ).…”
Section: Calcimimetic Treatment For Hypercalcaemic Disorders Of the Cmentioning
confidence: 97%
“…Thus, recent in vitro studies have shown that cinacalcet improves the signalling responses of HEK293 cells stably expressing the CaS receptor (HEK–CaS receptor), which have been transiently transfected with FHH2‐associated Gα 11 mutants (Babinsky et al ., ; Gorvin et al ., ). Indeed, nanomolar doses of cinacalcet were demonstrated to rectify the impaired Ca 2+ i responses associated with loss‐of‐function Gα 11 mutations (Table ) (Babinsky et al ., ; Gorvin et al ., ). Moreover, siRNA knockdown studies showed that cinacalcet enhanced the signalling mediated by the FHH2 mutant Gα 11 proteins rather than by exerting indirect effects on endogenously expressed wild‐type Gα 11 proteins (Babinsky et al ., ).…”
Section: Calcimimetic Treatment For Hypercalcaemic Disorders Of the Cmentioning
confidence: 97%
See 3 more Smart Citations